Hospital-Skilled Nursing Facility Referral Linkage Reduces Readmission Rates Among Medicare Patients Receiving Major Surgery - Schoenfeld, Andrew J. (Surgery, 2016)
BACKGROUND: In the health reform era, rehospitalization following discharge may result in financial penalties to hospitals. The effect of increased hospital-skilled nursing facility (SNF) linkage on readmission reduction following surgery has not been explored. METHODS: To determine whether enhanced hospital-SNF linkage, as measured by the proportion of surgical patients referred from a hospital to a particular SNF, would result in reduced 30-day readmission rates for surgical patients, we used national Medicare data (2011-12) and evaluated patients who received one of five surgical procedures (coronary artery bypass grafting, hip fracture repair, total hip arthroplasty, colectomy, lumbar spine surgery). Initial evaluation was performed using regression modeling. Patient choice in SNF referral was adjusted for using instrumental variable (IV) analysis with distance between an individuals’ home and the SNF as the IV. RESULTS: A strong negative correlation (p<0.001) was observed between the proportion of selected surgical discharges received by a SNF and the rate of hospital readmission. Increasing the proportion of surgical discharges decreased the likelihood of rehospitalization (RC −0.04, 95% CI [−0.07, −0.02]). These findings were preserved in IV analysis. Increasing hospital-SNF linkage was found to significantly reduce the likelihood of readmission for patients receiving lumbar spine surgery, CABG and hip fracture repair. CONCLUSIONS: The benefits of increased hospital-SNF linkage appear to include meaningful reductions in hospital readmission following surgery. Overall, a 10% increase in the proportion of surgical referrals to a particular SNF is estimated to reduce readmissions by 4%. This may impact hospital-SNF networks participating in risk-based reimbursement models.